2017
DOI: 10.1111/ijpp.12340
|View full text |Cite
|
Sign up to set email alerts
|

Telehealth: misconceptions and experiences of healthcare professionals in England

Abstract: This study showed experience and awareness level to be still low especially among HCPs working in primary care. Barriers and misconceptions identified are still the same as those reported in the literature which highlights that they have not yet been addressed to facilitate telehealth implementation in the UK.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
50
0
4

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 60 publications
(56 citation statements)
references
References 21 publications
2
50
0
4
Order By: Relevance
“…In addition, the anonymity of telephone consultations has been found to encourage the sharing of personal information and development of a non-judgmental attitude during consultations (Heckemann, Wolf, Ali, Sonntag, & Ekman, 2016). This counters common misconceptions that telerehabilitation is an "impersonal" mode of service delivery (Kayyali et al, 2017) and instead suggests that the conversational nature of consultations can facilitate an increased emphasis on behavior change support and exercise adherence.…”
Section: Technology Provide S Opp Ortunitie S For Remotely-deliverementioning
confidence: 97%
“…In addition, the anonymity of telephone consultations has been found to encourage the sharing of personal information and development of a non-judgmental attitude during consultations (Heckemann, Wolf, Ali, Sonntag, & Ekman, 2016). This counters common misconceptions that telerehabilitation is an "impersonal" mode of service delivery (Kayyali et al, 2017) and instead suggests that the conversational nature of consultations can facilitate an increased emphasis on behavior change support and exercise adherence.…”
Section: Technology Provide S Opp Ortunitie S For Remotely-deliverementioning
confidence: 97%
“…Para minimizar as desigualdades de acesso aos serviços de saúde e aumentar a resolutividade da atenção primária, o Brasil segue a tendência global de desenvolvimento e disseminação da telessaúde, também denominada de telemedicina ou e-saúde, sendo líder na implementação de projetos de grande escala 5,6 . A telessaúde tem sido cada vez mais incorporada como prática rotineira nos serviços de saúde em todo o mundo [7][8][9] . Todavia, ainda existe grande variabilidade na prestação dos serviços e na concepção que profissionais de saúde e usuários declaram sobre o tema 9 .…”
Section: Introductionunclassified
“…A telessaúde tem sido cada vez mais incorporada como prática rotineira nos serviços de saúde em todo o mundo [7][8][9] . Todavia, ainda existe grande variabilidade na prestação dos serviços e na concepção que profissionais de saúde e usuários declaram sobre o tema 9 . Mesmo na Inglaterra, onde o Serviço Nacional de Saúde definiu uma política própria sobre o tema, existem barreiras ao funcionameno pleno das atividades e receio dos médicos diante das novas relações estabelecidas 7 .…”
Section: Introductionunclassified
“…Our recent survey also found that, amongst people with knee and/or hip OA, there was no evidence that age and level of education influenced interest in receiving exercise from a physical therapist via video [36]. These findings counter commonly-held misconceptions of telehealth, namely that it may be most suitable for people who are younger and/or highly educated, and are therefore "technology-savvy" [37,38]. Our findings suggest that people of varying ages, and those with high or low levels of education, benefitted just as much with internet-delivered care.…”
Section: Moderators Of the Effect Of The Intervention On Change In Phmentioning
confidence: 68%